Management plan for Nonglom Wetlands, Samakhyxai, Attepeu Province, Lao PDR (2024-2029) - Mam, Kosal; Xaydala, Viengxai (2024)
This report outlines the management plan for the Nong Lom (NL) wetlands, a vital resource supporting local livelihoods. Nong Lom features a permanent lake surrounded by agricultural and residential areas. During the dry season, the lake’s open water spans approximately 20 hectares, with dimensions of about 350 meters by 2,400 meters. Water depths vary seasonally, ranging from 0.5 meters during the dry season to 1.5 meters during the wet season. A dirt road encircles the lake, particularly to the northeast, where rice paddies and cash crop fields extend beyond the road’s perimeter. Nong Lom serves as a key fishing ground, a water source for farming, and a provider of various environmental services. The management plan aims to guide the local community in revitalizing these services, thereby enhancing their livelihoods. The long-term objective is to restore the ecosystem functions, habitats, and biodiversity of the Nong Lom wetlands.